Preparation of TiO2 pigment from ilmenite ore concentrate by molten alkaline process - Thi Thao Nguyen; Ky Nam Pham; Thi Hinh Dinh; Vu Diem Ngoc Tran; Aman Ullah (Vietnam Journal of Science, Technology and Engineering, 2023)
TiO2 pigment production from an ilmenite concentrate via a molten alkaline process was investigated. The ilmenite concentrate (54.19% TiO2) was first roasted in the molten NaOH system at various temperatures ranging from 600 to 800°C while the mass ratio of NaOH/ilmenite was varied within the range of 0.8-1.2 for 1 hour. The achieved roasted efficiency was up to 93.93% at a temperature of 700°C and NaOH/ilmenite ratio of 1:1. The roasted product was first leached in water and then in a solution of HCl 20% at 50ºC for 2 hours. The TiOCl2 solution was hydrolysed at 95ºC for 2 hours. Precipitation of the hydrolysis process was then calcinated at 800ºC. The final obtained product contained up to 96.37% of TiO2. Ilmenite can be used as a raw material in a molten alkaline process. It is obvious that not only high purities of TiO2 could be achieved, but also the reduction of waste materials, raw materials, energy, and time.